Surgical Outcomes of the Endoscopic Endonasal Transsphenoidal Approach for Anterior Skull Base Lesions: Experience in Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction:The endoscopic endonasal approach is a minimally invasive surgical technique for removal of skull base lesions by using nose and sinuses as natural corridors. This study represents our institutional experience with endoscopic endonasal trans-sphenoidal approach for anterior skull base lesions.Objective: To find out surgical outcomes of endoscopic endonasal trans-sphenoidal approach for treatment of anterior skull base lesions.Materials and Methods: Cross-sectional observational study of 38 consecutive patients who underwent endoscopic endonasal trans-sphenoidal surgery for anterior skull base lesions in Combined Military Hospital, Dhaka from July 2013 to June 2017.Results:This study included 16 men and 22 women, ranging from 24 to 68 years of age where median was 38 years. Common presentations were visual disorder (60%), headache (30%), features of pituitary apoplexy (5%), Cushing disease (0.35%), acromegaly (0.7 %), galactorrhoea (0.35%). Radiological evaluation revealed intrasellar (12), sellar and suprasellar (22), sellar and parasellar (1), tuberculum sella and planum sphenoidale (3), clival (1) lesions. Recurrent cases (3/38) were nonfunctioning pituitary macroadenoma, prolactinoma, and growth hormone secreting macroadenoma. The surgical resection in relation to post op imaging were 45% as gross total resection, near-total in 35%, subtotal in 15%, and partial in 5%. We found fifteen patients experienced improvement in visual acuity, while one patient worsened. Common complications were transient diabetes insipidus (53%), new pituitary deficit (35%), endonasal adhesions (20%), and cerebrospinal fluid leak (5%). Surgical mortality was (0.35%). The histological diagnoses included twenty-eight pituitary adenomas, five craniopharyngioma, three meningioma, one Rathke’s cleft cyst and one clival chordoma.Conclusion: Endoscopic endonasal transsphenoidal surgery is a valuable treatment option for an anterior skull base lesion.Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 66-68